Effect of Precursor Stacking Structure on the Phase Formation and Efficiency of Cu2ZnSnS4 Solar Cell Prepared by Sulfurization of Cu-Zn-Sn Metal Precursors with H2S Gas - Lee, Jung Hun; Choi, Heon Jin; Kim, Won Mok; Jeong, Jeung Hyun; Park, Jong Keuk (AMER SCIENTIFIC PUBLISHERS, 2015)
The effect of precursor stacking structure on the phase formation and efficiency of Cu2ZnSnS4 (CZTS) thin film solar cells prepared by sulfurization of sputtered Cu-Zn-Sn metal precursors with H2S gas was investigated. Precursors with different stacking structures of (Cu, Zn, Sn), (Zn, Sn)/Cu and Zn/(Cu, Sn) were deposited by sputtering Cu, Zn, and Sn metal targets. The surface morphology and composition of the sulfurized precursors with H2S were observed to be critically dependent on the precursor stacking structure. For the CZTS film prepared by sulfurization of a (Cu, Zn, Sn) precursor, non-uniform surface morphology with different atomic concentration was observed. On the other hand, uniform grained surface morphology appeared in the CZTS films obtained by sulfurization of (Zn, Sn)/Cu and Zn/(Cu, Sn) precursors. The Zn/(Cu, Sn) precursor induced more dense surface microstructure with lower porosity in CZTS film. The solar cell performance of CZTS thin films was also affected by the stacking structure of precursor. In contrast to the CZTS thin film prepared with (Cu, Zn, Sn) precursor showing lower efficiency (similar to 0.8%), the CZTS solar cell fabricated with Zn/(Cu, Sn) precursor showed higher efficiency of 2.64%. This phenomenon was due to the change in the microstructure and secondary phase formation during sulfurization of metal precursors with H2S gas.
Keywords: THIN-FILMS; SULFUR-CONTENT; EQUILIBRIA